Complement Therapeutics in the Multi-Organ Donor: Do or Don't? - van Zanden, Judith E.; Jager, Neeltina M.; Daha, Mohamed R.; Erasmus, Michiel E.; Leuvenink, Henri G. D.; Seelen, Marc A. (Frontiers in Immunology, 2019)
Over the last decade, striking progress has been made in the field of organ transplantation, such as better surgical expertise and preservation techniques. Therefore, organ transplantation is nowadays considered a successful treatment in end-stage diseases of various organs, e.g. the kidney, liver, intestine, heart, and lungs. However, there are still barriers which prevent a lifelong survival of the donor graft in the recipient. Activation of the immune system is an important limiting factor in the transplantation process. As part of this pro-inflammatory environment, the complement system is triggered. Complement activation plays a key role in the transplantation process, as highlighted by the amount of studies in ischemia-reperfusion injury (IRI) and rejection. However, new insight have shown that complement is not only activated in the later stages of transplantation, but already commences in the donor. In deceased donors, complement activation is associated with deteriorated quality of deceased donor organs. Of importance, since most donor organs are derived from either brain-dead donors or deceased after circulatory death donors. The exact mechanisms and the role of the complement system in the pathophysiology of the deceased donor have been underexposed. This review provides an overview of the current knowledge on complement activation in the (multi-)organ donor. Targeting the complement system might be a promising therapeutic strategy to improve the quality of various donor organs. Therefore, we will discuss the complement therapeutics that already have been tested in the donor. Finally, we question whether complement therapeutics should be translated to the clinics and if all organs share the same potential complement targets, considering the physiological differences of each organ.